Adaptation science and policy in China's agricultural sector. (21st June 2016) - Rogers, Sarah
Abstract : In recent years, China's central government has begun to articulate its adaptation policy and to identify measures to adapt the nation's agriculture to changing precipitation patterns, higher temperatures, and extreme events. These developments are occurring at a time when the agricultural sector is in flux: while the major grain crops—rice, wheat, and corn—are still central to food security, many smallholder farmers have shifted away from land‐intensive production to growing higher‐value, labour‐intensive horticultural products, such as fruit and vegetables. In addition, new forms of agriculture are emerging because of out‐migration and land transfers. This review introduces the adaptation policy context for agricultural adaptation in China and reviews existing research on impacts and adaptation. It then discusses how well existing research and policy actually reflect the challenges of adapting China's farms to climate change. Four issues are discussed which together suggest that current science and policy very poorly reflect challenges on the ground: the framing of agriculture as a relatively homogeneous sector; the absence of any vulnerability assessments attuned to local contexts; a bias toward large‐scale engineering solutions; and insufficient consideration of local government capacity. WIREs Clim Change 2016, 7:693–706. doi: 10.1002/wcc.414 This article is categorized under: Vulnerability and Adaptation to Climate Change > Learning from Cases and Analogies